The network approach: A path to decolonize mental health care - Rediet Emebet Getnet Alemu; Tom L. Osborn; Christine M. Wasanga; Christine M. Wasanga (Frontiers Media S.A., 2023)
The violent colonial history of psychiatry in Africa prevents individuals from help-seeking. Because of this history, mental health care is now stigmatized, and clinical research, practice, and policy fail to capture the salient features of distress across African communities. If we are to transform mental health care for all, we must adopt decolonizing frameworks to ensure mental health research, practice, and policy are enacted in a manner that is ethical, democratic, critical, and serves the needs of local communities. Here, we present that the network approach to psychopathology as an invaluable tool in achieving this purpose. The network approach recognizes mental health disorders not as discrete entities, but rather as dynamic networks that are made of psychiatric symptoms (called nodes) and the relationships between these symptoms (called edges). This approach can pave a path to decolonizing mental health care by alleviating stigma, allowing context-based understanding of mental health and mental health problems, opening new avenues for (low-cost) mental health care and empowering local researchers to pioneer context-based knowledge production and treatment.